Effect of the axial force on shear and flexural strength of masonry spandrels - A. Sandoli; B. Calderoni; G. P. Lignola; A. Prota (Bulletin of Earthquake Engineering, 2023)

Correction to: “Predictive hybrid fragility models for urban scale seismic assessment: a case study in Basilicata Region (Italy) - A. Sandoli; G. Pacella; B. Calderoni; G. Brandonisio; G. P. Lignola; A. Prota (Bulletin of Earthquake Engineering, 2023)

Predictive hybrid fragility models for urban scale seismic assessment: a case study in Basilicata Region (Italy) - A. Sandoli; G. Pacella; B. Calderoni; G. Brandonisio; G. P. Lignola; A. Prota (Bulletin of Earthquake Engineering, 2023)

Seismic vulnerability assessment of minor Italian urban centres: development of urban fragility curves - A. Sandoli; B. Calderoni; G. P. Lignola; A. Prota (Bulletin of Earthquake Engineering, 2022)
This paper presents a novel hybrid-based methodology devoted to develop urban fragility curves and damage probability matrices to predict likelihood seismic damage scenarios for small and medium Italian urban centres, considering URM buildings only. The concept of urban fragility curve consists of a single curve mean-representative of the seismic fragility of an entire area accounting for the combinations of building classes and their percentage, then they differ from those typological. The methodology has been developed with reference to Rocca di Mezzo, a small Italian urban centre located in the central Apennine area, Italy. Based on CarTiS inventory, building classes have been firstly recognized and urban fragility curves, representative for damage scenarios at Ultimate Limit State, developed. To predict damage scenarios from low to high-intensity earthquakes, an approach to define multi-damage urban fragility curves and damage probability matrices has been also presented. To this aim, a damage scale suffered by building classes has been defined by converting the final outcomes of the AeDES form (used in Italy for post-earthquake surveys) in the damage levels provided by the European Macroseismic Scale (EMS98). Data coming from urban fragility curves have been compared with the actual damage scenario recorded in Rocca di Mezzo after the 2009 L’Aquila’s earthquake, in terms of both peak-ground acceleration and Mecalli-Cancani-Sieberg scale. The achieved results showed a good accordance between theoretical predictions and actual damage scenarios, coherent also with the damage scenarios occurred in other Italian historical centres hit by severe earthquakes over the years. Thus, the methodology can provide a first important indicator to support the development of emergently plans devoted to identify priority of interventions in such areas particularly vulnerable with respect to others.

Fragility curves for Italian URM buildings based on a hybrid method - A. Sandoli; G. P. Lignola; B. Calderoni; A. Prota (Bulletin of Earthquake Engineering, 2021)
A hybrid seismic fragility model for territorial-scale seismic vulnerability assessment of masonry buildings is developed and presented in this paper. The method combines expert-judgment and mechanical approaches to derive typological fragility curves for Italian residential masonry building stock. The first classifies Italian masonry buildings in five different typological classes as function of age of construction, structural typology, and seismic behaviour and damaging of buildings observed following the most severe earthquakes occurred in Italy. The second, based on numerical analyses results conducted on building prototypes, provides all the parameters necessary for developing fragility functions. Peak-Ground Acceleration ( PGA ) at Ultimate Limit State attainable by each building’s class has been chosen as an Intensity Measure to represent fragility curves: three types of curve have been developed, each referred to mean, maximum and minimum value of PGA s defined for each building class. To represent the expected damage scenario for increasing earthquake intensities, a correlation between PGA s and Mercalli-Cancani-Sieber macroseismic intensity scale has been used and the corresponding fragility curves developed. Results show that the proposed building’s classes are representative of the Italian masonry building stock and that fragility curves are effective for predicting both seismic vulnerability and expected damage scenarios for seismic-prone areas. Finally, the fragility curves have been compared with empirical curves obtained through a macroseismic approach on Italian masonry buildings available in literature, underlining the differences between the methods.